The Distributional Shape of Unemployment Duration: A Reply - Addison, John T.; Portugal, Pedro (The Review of Economics and Statistics, 1992)
McDonald, James B., and Richard J. Butler, Some Generalized Mixture Distributions with an Application to Unemployment Duration, this REVIEW 69 (May 1987), 232-240. Podgursky, Michael, and Paul Swaim, Duration of Joblessness Following Displacement, Industrial Relations 26 (Fall 1987), 213-226. Prentice, Ross L., A Log Gamma Model and Its Maximum Likelihood Estimation, Biometrika 61 (Dec. 1974), 539-544. Swaim, Paul, and Michael Podgursky, Advance Notice and Job Search: The Value of an Early Start, Journal of Human Resources 25 (Spring 1990), 148-178.